Methods Without Formwork Molding of Reinforced Concrete Products - Irina Yurevna Kovtun (Genius Journals, 2022)
The article discusses the technology of without formwork molding of reinforced concrete products. Various forming technologies are given and cement consumption is analyzed, as well as the advantages of this technology
Keywords: Without formwork forming of reinforced concrete; extrusion